2021
DOI: 10.3390/diagnostics11122317
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Application of Volatile Organic Compounds as Potential Biomarkers for Detecting Digestive Neoplasia: A Systematic Review

Abstract: Volatile organic compounds (VOCs) are part of the exhaled breath that were proposed as non-invasive breath biomarkers via different human discharge products like saliva, breath, urine, blood, or tissues. Particularly, due to the non-invasive approach, VOCs were considered as potential biomarkers for non-invasive early cancer detection. We herein aimed to review the data over VOCs utility in digestive neoplasia as early diagnosis or monitoring biomarkers. A systematic literature search was done using MEDLINE vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
(183 reference statements)
0
16
0
Order By: Relevance
“…[21]. The nature of these diseases related special smells is caused by different VOCs, which is demonstrated by the nobel prize laureate that Linus Pauling's pioneer work on the breath analysis in 1971 using gas-liquid partition chromatography [22]. In the past 50 years, thousands of volatile biomarkers, i.e., VOCs, associated with various diseases or lesions, have been identified and classified from multi-body sources (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[21]. The nature of these diseases related special smells is caused by different VOCs, which is demonstrated by the nobel prize laureate that Linus Pauling's pioneer work on the breath analysis in 1971 using gas-liquid partition chromatography [22]. In the past 50 years, thousands of volatile biomarkers, i.e., VOCs, associated with various diseases or lesions, have been identified and classified from multi-body sources (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that acetone, ammonia, benzaldehyde, butanal, butyric acid, decane, dimethyl/hydrogen sulfide, dimethyl/undecane, ethylbenzene, 1,2,3-tri-methylbenzene, 1,2-di-methylbenzene, furfural, hexanoic acid, hexane/hexanal, isoprene, phenol, pentanoic acid, p-xylene, and tetradecane are associated with digestive cancers. 51 Metabolites can be absorbed in the blood and exhaled directly. They may also be absorbed and further metabolized in liver, kidney, and other internal organ systems and their microbiomes and exhaled as final stable states.…”
Section: Discussionmentioning
confidence: 99%
“…Although most commonly used biomarkers are blood-based, CSF, urine, saliva or breath are other frequent sources of biological material for diagnostics purposes. In this issue, Dima et al [ 4 ] performed a systematic review of the use of volatile organic compounds (VOCs) in exhaled breath as non-invasive biomarkers in digestive neoplasia.…”
Section: Discussionmentioning
confidence: 99%